HOW TO MOVE STUDENTS FORWARD FROM ANALYTICAL AND SYNTOPICAL READERS TO PUBLIC SPEAKERS WHILE TEACHING ENGLISH AS A SECOND LANGUAGE - Kuprashvili, Violetta (European Scientific Journal, ESJ, 2014)
To make students good readers and good speaker can be achieved through development of the receptive, productive and interactive skills and competencies through variety of methods and activities. The work â€œHow to Read a Bookâ€ by Mortimer Jerome Adler and Charles Van Doren provides a wide choice of concepts and theories and shows importance of moving the students from analytical reading to higher level of syntopical reading and the transition from good reading skills to public speaking. Based on the important concepts of the book the paper analyses: a. Analytical reading: how it strengthens and broadens the studentsâ€™ knowledge about argumentation, analyze and evaluation through examples and step-by â€“step activities. b. Syntopical reading: how the students compare and contrast different works, demonstrate insight, articulate sophisticated ideas, learn effective ways to analyze, evaluate, and integrate ideas from a single source or synthesize the work from multiple sources to formulate and support original arguments. c. Transition and correlation between reading skills to speaking persuasively in order to deliver powerful, well-organized speech and present it to the audience; how to appreciate and emulate the speeches of great orators. The paper provides methodological guides, judgments, tested activities and examples to make the students in-depth readers and confident, competent interpersonal communicators.